Advancing women’s mental health services in Qatar - Majid Alabdulla (12051430) (2025)
This article provides a narrative overview of the development of women’s mental health services in Qatar. The country has made notable advancements, driven by progressive health policies and a focus on gender-sensitive care. Key initiatives include the development of specialised services, the integration of mental health into primary care and the implementation of targeted training programmes for healthcare professionals. The establishment of a fellowship programme in women’s mental health and the incorporation of gender considerations into national clinical practice guidelines further underscore the country’s commitment. Addressing remaining gaps through innovation, inclusivity and collaboration will be vital to ensuring comprehensive mental healthcare for all women. Other Information Published in: BJPsych International License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1192/bji.2025.10070